Effect of Berry Extracts and Bioactive Compounds on Fulvestrant (ICI 182, 780) Sensitive and Resistant Cell Lines. (31st December 2012) - Woode, Denzel R.; Aiyer, Harini S.; Sie, Nicole; Zwart, Alan L.; Li, Liya; Seeram, Navindra P.; Clarke, Robert
Abstract : Fulvestrant (ICI 182, 780; ICI) is approved for the treatment of advanced metastatic breast cancer that is unresponsive to other endocrine therapies. Berries are frequently consumed for their antioxidant, anti-inflammatory, and anticancer potential. In this study, we tested the efficacy of two berry extracts (Jamun-EJAE and red raspberry-RRE) and their bioactive compounds (Delphinidin-Del and Ellagic acid-EA) to inhibit cell proliferation with or without a sublethal dose of ICI in various breast cancer cell lines. ICI-sensitive (LCC1, ZR75-1, and BT474) and -resistant (LCC9, ZR75-1R) cells were subjected to treatment with berry extracts alone (0.1–100 μ g/mL) or with a sub-lethal dose of ICI (50 dose; 1 nM for sensitive; 1 μ M for resistant cells). Extracts and Del enhanced the effect of ICI in sensitive ZR75-1 and BT474 cells primarily in an additive fashion (measured by relative index (RI) 1). In ZR75-1R cells, both EJAE and RRE synergistically enhanced the effects of ICI (15–50%; P < 0.05 ; RI > 1 ). EA, in doses tested, did not have any significant effects on any of the cell lines. Finally, we found that the extracts were more effective at lower, physiologically relevant concentrations than at higher experimental doses.